Bilateral open-angle glaucoma in a young female with Desbuquois syndrome - Isha Chaturvedi,; Kumudini Sharma,; Vaibhav Jain, (Indian Journal of Case Reports, 2021)
Desbuquois dysplasia is characterized by the presence of short stature, short extremities, joint laxity with frequent dislocation, osteopenia, vertebral abnormalities, distinctive facial characteristics, and other abnormalities including myopia and glaucoma. A variant form of Desbuquois type skeletal dysplasia (DBQD), the Kim variant, has also been described and is characterized by short stature, joint, and minor facial anomalies. Here, we report a case of bilateral open-angle glaucoma and high myopia occurring in a young female who presented with Desbuquois syndrome, a rare type of osteochondrodysplasia. The patient presented to the ophthalmology clinic with persistent eye pain and unstable refractive error. Her preliminary examination revealed raised intraocular pressure, high myopia, and skeletal deformities. A complete systemic examination and genetic workup suggested DBQD, Kim variant. With no detailed ophthalmic reports of such patients existing in the literature, it is important that such patients undergo a complete ophthalmic survey to rule out glaucoma, high myopia, and strabismus.